Assessment of shade matching using visual and instrumental methods: An In vivo study - Jesmy K Antony; Liza George; Josey Mathew (Wolters Kluwer Medknow Publications, 2021)
Aims: This study aimed to compare the shade selection of natural teeth using visual method, digital photographic method, spectrophotometric method, and using an intraoral scanning device. Settings and Design: A study was conducted at the department of conservative dentistry and endodontics. Subjects and Methods: Right maxillary central incisors of ten subjects without caries, defects, or any restorations were selected for the study. Shade selection was done from the middle third of the labial surface of the tooth. In visual method the shade selection was carried out by an experienced clinician and in digital photographic method by a technician with gray cards as background and software analysis the other methods were spectrophotometric method and using an intraoral scanning device. Statistical Analysis Used: Statistical analysis was done using the nonparametric Kruskal-Wallis test. Post hoc was done using the Mann-Whitney U-test. Results: When the shades selected using the four methods were compared, with spectrophotometric methods, statistically significant differences were found for visual and digital photographic methods. Conclusions: Whenever possible, it is better to combine visual and instrumental methods so as to reduce the subjective errors that can happen while using the visual method alone. Among the instrumental methods, the less expensive digital photographic method can be opted for instead of the more sophisticated methods with chances of minimal errors.